DUBLIN [Degree of Ulcerative colitis Burden of Luminal Inflammation] Score, a Simple Method to Quantify Inflammatory Burden in Ulcerative Colitis. (26th March 2019) - Rowan, Catherine R; Cullen, Garret; Mulcahy, Hugh E; Sheridan, Juliette; Moss, Alan C; Ryan, Elizabeth J; Doherty, Glen A
Abstract: Background and Aims: Endoscopic scores of local severity do not reflect disease extent, or disease burden. The DUBLIN score is a simple bedside clinical score that estimates inflammatory burden using both disease severity and extent. As the need to personalize therapy for ulcerative colitis [UC] patients increases, a score accurately assessing disease burden will be of great relevance. The aim of this study was to assess the clinical utility of the DUBLIN score by comparing its performance with objective biomarkers. Methods: The DUBLIN score was calculated as a product of the Mayo Endoscopic Score [0–3] and disease extent [E1–E3]. Correlation with objective biomarkers was performed in a retrospective 'discovery cohort'. A 'validation cohort was recruited from a single centre, where clinical outcomes, colectomy rate, and biochemical data were collected prospectively. Results: The discovery cohort included 70 patients with UC. The DUBLIN score correlated significantly with faecal calprotectin [FCP] levels [ r = 0.394; p < 0.01]. Receiver operating characteristic [ROC] analysis using FCP>50μg/g showed a higher area under the ROC curve [AUC] with the DUBLIN score [AUC = 0.76] than with the Mayo Score [AUC = 0.73]. The validation cohort included 41 patients. Patients with a high inflammatory burden [DUBLIN >3] had higher C-reactive protein and FCP, and lower albumin than patients with a low inflammatory burden. A high DUBLIN score was associated with an increased risk of treatment failure. [hazard ratio 2.98 95%, confidence interval 1.002–8.87; p = 0.049] Conclusion: The DUBLIN score is a simple measure of inflammatory burden, which correlates with objective inflammatory markers and is associated with clinical outcomes, such as treatment failure. The DUBLIN score has the potential to assist in personalizing therapy for patients with UC.